2020
DOI: 10.1182/blood.2019003084
|View full text |Cite
|
Sign up to set email alerts
|

Targeting aberrant DNA hypermethylation as a driver of ATL leukemogenesis by using the new oral demethylating agent OR-2100

Abstract: Adult T-cell leukemia-lymphoma (ATL) is an aggressive hematological malignancy of CD4+ T-cells transformed by human T-cell lymphotropic virus-1 (HTLV-1). Most HTLV-1-infected individuals are asymptomatic and only 3-5% of carriers develop ATL. Here, we describe the contribution of aberrant DNA methylation to ATL leukemogenesis. HTLV-1-infected T-cells and their uninfected counterparts were separately isolated based on CADM1 and CD7 expression status, and differentially methylated positions (DMPs) specific to HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 48 publications
(62 reference statements)
3
58
0
Order By: Relevance
“…These environmental stimuli provoke epigenetic changes, which regulate the biological modification of DNA without changing the sequences and subsequently influence the degree of gene expression [98]. The importance of epigenetic modification has been observed in various cutaneous skin malignancies, such as squamous cell carcinoma [99], melanoma [100], and lymphomas [101].…”
Section: Epigenetic Modification In Liposarcomamentioning
confidence: 99%
“…These environmental stimuli provoke epigenetic changes, which regulate the biological modification of DNA without changing the sequences and subsequently influence the degree of gene expression [98]. The importance of epigenetic modification has been observed in various cutaneous skin malignancies, such as squamous cell carcinoma [99], melanoma [100], and lymphomas [101].…”
Section: Epigenetic Modification In Liposarcomamentioning
confidence: 99%
“…A recent study investigating ATLL in Japanese subjects identified the accumulation of aberrant DNA methylation, which was correlated with development and progression. 28 Based on genomic findings from Japanese subjects with ATLL, it is believed that DNA hypermethylation status in ATLL cells is not related to genetic events. 10 Although the methylation pattern of ATLL in North American subjects remains unclear, gene expression profiling distinguished North American and Japanese cases, suggesting that they have different properties.…”
Section: Reg I Onal D Ifferen Ce S In Atllmentioning
confidence: 99%
“…They observed tumor reduction by all three HMAs, albeit with variable hematopoietic toxicity (least to most; AZA, OR21, DAC) and hypomethylation of THEMIS TSS200 (least to most; AZA, OR21, DAC) at the doses used. With a view to potential long-term oral therapy, OR-21 was used (intraperitoneally, twice weekly for 100 days) to treat mice bearing peritoneal hCD45 1 / CADM1 1 xenografts established by inoculating peripheral blood mononuclear cells from a patient with chronic ATL. OR21 produced a striking improvement in morbidity and mortality (see figure panel B).…”
mentioning
confidence: 99%
“…10 OR-21 was shown to be bioavailable following intraduodenal administration to macaques and is potentially another oral HMA. 1 The cell death can be overcome in vitro and in vivo by interleukin-2 (IL-2) supplementation. This work builds on the previous observation of the same group, which showed 2 subpopulations of Tregs with distinct phenotypes in AA: Treg A, with a naive phenotype (low proliferative index), and Treg B, with a memory phenotype (moderate/high proliferative index) that correlated with response to immunosuppressive therapy (IST).…”
mentioning
confidence: 99%
See 1 more Smart Citation